1978
DOI: 10.1111/j.1748-5827.1978.tb05559.x
|View full text |Cite
|
Sign up to set email alerts
|

Short–term antimicrobial therapy–a pilot compliance study using ampicillin in dogs

Abstract: A short–term drug compliance study, using ampicillin in dogs, was carried out. The results indicated that three out of four owners do not follow the instructions of veterinarians relating to the oral administration of ampicillin at home. This study also showed that owners of pets wish to treat their animals according to the instructions issued by the veterinarians. The causes of non–compliance do not appear to involve factors such as the animal getting better or the owner's inability to give the antibiotic ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Studies 41,42 involving owner compliance in veterinary medicine have investigated short-term use of antimicrobials and suggested that compliance is a problem. An important determinant for adherence was that animal owners felt that the veterinarians spent enough time during the consultation.…”
Section: Patient Health-a Reviewmentioning
confidence: 99%
“…Studies 41,42 involving owner compliance in veterinary medicine have investigated short-term use of antimicrobials and suggested that compliance is a problem. An important determinant for adherence was that animal owners felt that the veterinarians spent enough time during the consultation.…”
Section: Patient Health-a Reviewmentioning
confidence: 99%
“…The degree of compliance required to effect an adequate therapeutic outcome of antibacterial drug treatment is, however, difficult to assess. In the study by Bromzon (1978), 13 owners were questioned as to why there was more medicine left than should have been the case. The reason given by owners for being unable to follow the instructions was that because they were at work during the day, they were unable to treat the dog in the middle of the day.…”
Section: Dbscussionmentioning
confidence: 99%
“…Coincidental with the optimization of the PK/pharmacodynamic (PD) relationship through the maintenance of prolonged effective plasma concentrations are the patient benefits to be derived from requiring only intermittent administration by s.c. injection. Thus, not only would any potential problems and stress associated with repeated daily oral dosing be avoided, but it would also facilitate improved compliance with the prescribed dosing regimen by both owner and patient (Bomzon, 1978; Barter et al. , 1996; Grave & Tanem, 1999).…”
Section: Introductionmentioning
confidence: 99%